The Application of Historic Building Information Modelling (HBIM) to Cultural Heritage: A Review - Lucy J. Lovell; Richard J. Davies; Dexter V. L. Hunt (Heritage, 2023)
Historic Building Information Modelling (HBIM) is the application of BIM, a digital modelling and information management technique, to assets of historical significance, otherwise known as Cultural Heritage (CH). The adoption of BIM for CH is justified by government mandates and acknowledgement by leading heritage institutions that there is a need to utilise digital tools for heritage management. This paper establishes the current state of HBIM implementation within CH as well as research trends to date via a review of the existing literature. Geometric modelling was found to be the topic of very early research into HBIM, with particular focus given to improving the accuracy and efficiency of modelling. Thus, methods for improving modelling were evaluated. HBIM as an information management tool is discussed including the issues encountered, such as data storage and insufficient existing tools, as well as key information requirements proposed in the literature. An evaluation of key HBIM case studies found limited evidence of the created models being used in practice and an overall lack of consideration of the information needs. It was determined that the implementation of HBIM is limited by a lack of defined information requirements, and standardisation regarding the method of implementation.